Correlation Of (D- Dimer), (LDH) And (C RP) Levels With COVID-19 Infection - Saeed Hussein, Ibrahim Mohammed; Hameed Mahmoud, Jalank; Wahhab, Cheia Majeed (Clinical Medicine And Health Research Journal, 2023)
100 samples were taken from people infected with Covid 19 virus, where the infection was diagnosed by taking nasal samples using special sterile cotton swabs, then the infection was confirmed using a PCR machine. After confirming the infection, 52 samples were taken from males (52%) and 48 samples from females (48%) of different ages, in general, the results showed that 78% of the infected people had an increase in CRP and 46% of the infected people had an increase in D. dimer above the normal level While 36% had an increased LDH. Then the levels of LDH, D. dimer and CRP were measured using the Vitec device, the results showed that the patients aged over 50 years in both sexes were more affected by the infection than the patients aged less than 50 years, as they showed that the percentage of infection severity was in the elderly more and that the percentage of infection was more High levels of LDH, D. dimer and CRP in males were more than females and this may be affected by sex hormones